The scarlet shedder ebook - Pilkey, Dav (Dog Man, 2024)
Our canine superhero returns in DOG MAN: THE SCARLET SHEDDER, the suspenseful and hilarious twelfth graphic novel in the #1 worldwide bestselling series by award-winning author and illustrator Dav Pilkey! P.U.! Dog Man got sprayed by a skunk! After being dunked in tomato juice, the stink is gone but the scarlet red color remains. Now exiled, this spunky superhero must struggle to save the citizens who shunned him! Will the ends justify the means for Petey, who's reluctantly pulled back into a life of crime in order to help Dog Man? And who will step forward when an all-new, never-before-seen villain unleashes an army of A.I. robots? The fun and creativity continue with Dog Man with Love: The Official Coloring Book. And for more heartfelt graphic novel adventures, join Flippy and Li'l Petey in the Cat Kid Comic Club series. And don't forget the series that started it all: Captain Underpants!